New hybrid multiplanar cone beam computed tomography-laser-fluoroscopic-guided approach in cochlear implant surgery - Waldeck, Stephan; Schmidt, Sandra; von Falck, Christian; Chapot, René; Brockmann, Marc Alexander; Overhoff, Daniel (International journal of computer assisted radiology and surgery, 2022)
Cochlea implant surgery with proper positioning of the cochlear electrode can be challenging. Intraoperative real-time hybrid laser-fluoroscopic-guided navigation based on a multiplanar cone beam computed tomography (CBCT) dataset opens up the opportunity to immediate radiological control of primary electrode misalignments and offering new insights into the cochlea electrode insertion routes and favorable cochlear implant-insertion angle.